Herbivore–shrub interactions influence ecosystem respiration and biogenic volatile organic compound composition in the subarctic - Brachmann, Cole G.; Vowles, Tage; Rinnan, Riikka; Björkman, Mats P.; Ekberg, Anna; Björk, Robert G. (Biogeosciences, 2023)
Arctic ecosystems are warming nearly 4 times faster than the global average, which is resulting in plant community shifts and subsequent changes in biogeochemical processes such as gaseous fluxes. Additionally, herbivores shape plant communities and thereby may alter the magnitude and composition of ecosystem respiration and biogenic volatile organic compound (BVOC) emissions. Here we determine the effect of large mammalian herbivores on ecosystem respiration and BVOC emissions in two southern and two northern sites in Swedish Scandes, encompassing mountain birch (LOMB) and shrub heath (LORI) communities in the south and low-herb meadow (RIGA) and shrub heath (RIRI) communities in the north. Herbivory significantly altered BVOC composition between sites and decreased ecosystem respiration at RIGA. The difference in graminoid cover was found to have a large effect on ecosystem respiration between sites as RIGA, with the highest cover, had 35 % higher emissions than the next highest-emitting site (LOMB). Additionally, LOMB had the highest emissions of terpenes, with the northern sites having significantly lower emissions. Differences between sites were primarily due to differences in exclosure effects and soil temperature and the prevalence of different shrub growth forms. Our results suggest that herbivory has a significant effect on trace gas fluxes in a productive meadow community and that differences between communities may be driven by differences in shrub composition.